The Effectiveness of Vocab Acrostic Strategy in Teaching Vocabulary Mastery - Helmi, Muhammad (JOLLT Journal of Languages and Language Teaching, 2018)
This research is aimed to find out whether or not vocab acrostic effective in teaching Vocabulary at MTs. Islam Selaparang Putra Kediri Lombok Barat. This research is experimental research. The design used was one group pre-test post-test design. The sample was all population of the second grade students that consisted of 28 students. The Instrument was valid andreliable. The findings shows that t-test is (4,59) > t-table (2,057) at the significant level = 0,05 (95%) and N = 28 students. It means that, Alternative hypothesis (Ha) is accepted and Null hypothesis (Ho) is rejected. The mean score of post-test score is 76,71and pre-test score is 54,5. It can be concluded that Vocab Acrostic isÂ effective in teaching Vocabulary at MTs. Islam Selaparang Putra Kediri Lombok Barat in academic year2016/2017.